Teknologi Budidaya Maggot untuk Kelompok Pembudidaya Ikan “Panle Bersaudara”, Desa Danda Jaya, Barito Kuala - Noor Arida Fauzana; Pahmi Ansyari; Slamet Budianto; Ahmad Faisal Azhar (Universitas Muhammadiyah Semarang, 2024)
Community Service with the Community Partnership Program (PKM) scheme was carried out for the